Collins COBUILD key words for IELTS book 1 - Moore, Julie (HarperCollins Publishers, 2011)
The Collins COBUILD Key Words for IELTS series is a brand-new range of three graded books which contain the essential vocabulary students need to succeed in the IELTS exam